2016
DOI: 10.1007/s10877-016-9924-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microcirculatory video quality on the evaluation of sublingual microcirculation in critically ill patients

Abstract: We aimed to assess the impact of image quality on microcirculatory evaluation with sidestream dark-field (SDF) videomicroscopy in critically ill patients and explore factors associated with low video quality. This was a retrospective analysis of a single-centre prospective observational study. Videos of the sublingual microcirculation were recorded using SDF videomicroscopy in 100 adult patients within 12 h from admittance to the intensive care unit and every 24 h until discharge/death. Parameters of vessel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…At least 5 videos from different areas were recorded with adequate contrast and focus, and all efforts were made to avoid pressure artifacts. The image quality was checked offline [15], and videos of inadequate quality were discarded. Three videos per time-point were analysed offline with dedicated software (Automated Vascular Analysis 3.2, Microvision Medical, Amsterdam, NL) [16].…”
Section: Methodsmentioning
confidence: 99%
“…At least 5 videos from different areas were recorded with adequate contrast and focus, and all efforts were made to avoid pressure artifacts. The image quality was checked offline [15], and videos of inadequate quality were discarded. Three videos per time-point were analysed offline with dedicated software (Automated Vascular Analysis 3.2, Microvision Medical, Amsterdam, NL) [16].…”
Section: Methodsmentioning
confidence: 99%
“…The video acquisition technique is extensively described in previous papers [ 16 ]. For every session, videos from at least five different sites were registered trying to obtain a good video quality and to avoid artefacts that may affect flow or vessels density variables [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…New in this consensus is the requirement to have an objective measure (e.g., score) for the quality of the image based on the above considerations. Such objective quality scores have been developed and used in the literature and open the way for an impartial evaluation of the quality of the image to be embedded in software as a prerequisite for automatic analysis software [58][59][60]. We recommend that an objective quality score, such as that described by Massey et al, should be reported as part of the methods section in each applicable scientific paper.…”
Section: Recommendationsmentioning
confidence: 99%